SPK Pemilihan Resep Masakan dengan SAW dan Fitur Berbasis Lokasi Pada Android - Nabila Nabila; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The selection of recipes on digital recipes is now done manually by comparing recipes to get recipes that match the criteria. The selection of recipes manually is less effective because it takes a lot of time in the recipe selection process from a large number of recipes. Lack of information on where to buy ingredients is also a problem because finding the location of the providers of the required ingredients takes time and sometimes the information gets less precise so mistakes in finding the location of purchasing ingredients often occur. To overcome these problems, we need a decision support system that can solve the problem of choosing recipes and can provide location information to buy the materials needed for cooking. The recipe selection decision support system is implemented using Simple Additive Weighting (SAW) method in the selection of recipes equipped with location-based features to provide location information where to buy ingredients. The system runs on the Android platform to take advantage of location-based features (LBS) found on Android. The result of User Acceptance Testing (UAT) with calculation using Likert's Summated Rating (LSR) scaling technique obtained a total score of 804.